Digital Marketing Adoption among Female MSMEs in Dharmasraya: Profile, Platform Choices, and Challenges - Gusteti, Yesi; Tri Yuniko, Fauzi (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2025)
This research discusses the use of digital marketing platforms by women MSMEs in Dharmasraya. The objective of the research is to identify the profiles and factors influencing the use of digital marketing platforms by women MSMEs in Dharmasraya Regency. Data is not yet available for this area. This research uses descriptive statistics and multinomial logistic regression on 125 women MSMEs spread across 11 sub-districts in Dharmasraya Regency. Descriptive statistics show that Facebook is the most popular choice. Married status, Telkomsel provider, trading business, individual business type, easily accessible location, purpose of promotion, no website and never experienced fraud are the dominant indicators in the profile of women MSMEs. Multinomial Logistic regression analysis shows that the most influential variables are education, experience of fraud, number of children and business sector. The model comparing the choice of Istagram to Facebook is influenced by the last education, the lower number of children, the trade sector and never having experienced fraud. The age of MSMEs and the experience of never having experienced fraud have more influence on MSMEs using WA than on Facebook users. For WA Business, the higher education factor increases the likelihood of women MSMEs using WA Business compared to Facebook. As for Tiktok, none of the variables affect compared to Facebook users.